Mediterranean pasture dynamics: the role of germination (Journal of Vegetation Science, 1993)
pastures were arranged along a gradient of sensitivity to temperature on the arrival of the first persistent rain. This sensitivity was manifested in both the total germination success of the species and the germination time profile. The different germination patterns of the species can provide competitive advantages depending on the autumn weather conditions.